AB0465 Etanercept therapy in rheumatoid arthritis patients with moderate or severe disease activity. (23rd January 2014) - Iannone, F.; Ferraccioli, G.; Ferri, C.; Galeazzi, M.; Gerli, R.; Giacomelli, R.; Grassi, W.; Gorla, R.; Govoni, M.; Marchesoni, A.; Punzi, L.; Sarzi-Puttini, P.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is conventionally defined as moderate when the disease activity score assessed in 28 joints (DAS28) is ≥3.2, and high disease with DAS28 >5.1 Objectives: Aim of this analysis was to evaluate the rate of remission and LDA (low disease activity), in RA patients starting etanercept therapy with moderate disease activity in the real world settings Methods: The clinical records were retrospectively analysed from the Italian nationwide registry, called GISEA (Gruppo Italiano Studio Early Arthritis). RA patients with moderate (Mod-RA) and high (H-RA) disease activity (DAS28 >3.2) with incomplete response to conventional DMARDs and beginning a treatment with etanercept 50 mg/week subcutaneously (or 25 mg twice/week) over 10 years (2001-2010) were considered and compared. Clinical remission (DAS28 <2.6), LDA (DAS28 <3.2), HAQ, EULAR clinical response were assessed at 6 and 12 months of therapy, and etanercept survival rate at 1 and 4 years Results: 963 patients with moderate to severe RA were selected. Out of 963, 320 had Mod-RA and 633 H-RA. At 1 year, the rate of patients achieving DAS28 remission were significantly higher in Mod-RA (47.9%) than in H-RA (24.5%, p<0.001), and patients achieving LDA was significantly higher in Mod-RA (65.9%) than in H-RA (36.7%, p<0.001). "Good" EULAR response was significantly higher in Mod-RA (58.9%) than in H-RA group (36.7%) (p<0.01). Surprisingly, the retention rate of etanercept was significantly higher in H-RA patients (84.5%) than in Mod-RA patients (75.4%), both at 1 year (p<0.01) and at 4 years, 58.4% and 48.8%, respectively (p<0.01). Also the HAQ response was intriguing. In H-RA patients, mean HAQ score was 1.6 at baseline and 0.83 at 12 months (mean difference 0.77), while in Mod-RA patients, mean HAQ score was 1.01 at baseline and fell down at 0.55 after 6 months (mean difference 0.46, p=0.0001).Apparently patients starting with high disease activity have more room for improvement in HAQ, but the patients starting with moderate RA reach better absolute levels.Univariate and multivariate logistic regression analysis did not detect any predictor of response differentiating patients with H-RA from those with Mod-RA Conclusions: Consistently with previous reports, this preliminary data have provided evidence that in standard care setting Mod-RA patients had a high likelihood to achieve a DAS28 driven clinical remission as well as a condition of LDA when treated with etanercept Disclosure. This analysis was supported by Pfizer Inc. Disclosure of Interest: F. Iannone Grant/Research support from: Pfizer Inc., G. Ferraccioli: None Declared, C. Ferri: None Declared, M. Galeazzi: None Declared, R. Gerli: None Declared, R. Giacomelli: None Declared, W. Grassi: None Declared, R. Gorla: None Declared, M. Govoni: None Declared, A. Marchesoni: None Declared, L. Punzi: None Declared, P. Sarzi-Puttini: None Declared, G. Triolo: None Declared, G. Lapadula: None Declared